Dynamics and Thresholds of a Simple Epidemiological Model: Example of HIV/AIDS in Mali - Ouaténi Diallo; Yaya Koné; Jérôme Pousin (International Journal of Mathematics and Mathematical Sciences)
The dynamics of many epidemiological models for infectious diseases that spread in the sexually active population presents a crucial period: the period of the influx or recruitment of susceptible. In this paper, we assume that the recruitment of susceptible is done among the juvenile group. We propose a dynamical system to modelize the disease spread, and we study the dynamical behavior of this system. Then, the controllability of the system is studied. We prove that the survival rate allows to control the dynamic of the system. Numerical simulations are given to illustrate the results.